Physical and electrical properties' evaluation of SnS:Cu thin films. (1st February 2021) - Sebastian, S.; Kulandaisamy, I.; Valanarasu, S.; Shkir, Mohd; Ganesh, V.; Yahia, I. S.; Kim, Hyun-Seok; Vikraman, Dhanasekaran
ABSTRACT: This paper reports successful fabrication of copper-doped tin sulphide (SnS:Cu) thin films using nebulized spray pyrolysis. Different Cu doping concentrations (2, 4, 6, and 8 wt-%) were employed to coat SnS:Cu thin films. The fabricated SnS:Cu thin films were structurally confirmed by X-ray diffraction and Raman scattering analyses. Energy-dispersive X-ray result has proved Cu atom doping within the SnS matrix. Atomic force microscopy has identified topographical modifications on SnS:Cu thin films due to Cu doping concentration. UV-visible-NIR spectroscopy was used to derive the optical band gap in the range of 1.38–1.59 eV depending on Cu doping percentage. Hall Effect measurements were employed to analyze the electrical conductivity of SnS:Cu thin films. A p-n junction FTO/n–CdS/p–SnS:Cu/Al prototype device was constructed with photo response behaviour under dark and illumination circumstances.